Algoritma Forward Chaining dan Teorema Bayes Dalam Sistem Pakar Screening Parafilia - Ningrum, Anggi Faradhiba Puspa; Yahfizham, Yahfizham; Muliani, Aninda (STMIK Triguna Dharma, 2023)
Paraphilias are a group of disorders related to sexual activity that society considers strange or abnormal. This causes many people with paraphilia to experience ostracism and hide their condition. Even though social media and news report on the increasing phenomenon of paraphilia, there are still many people who don't know how to deal with this condition. Economic limitations and embarrassment discourage many people from visiting specialists such as psychologists, especially since most of them live in big cities. This makes it difficult for the public to access accurate information and early diagnosis. This factor causes people with possible paraphilia to be less aware of their condition and reluctant to seek treatment. This study uses additional methods such as forward chaining and Bayes' theorem to overcome the uncertainty of diagnosis and increase the level of accuracy. This expert system can assist the community in carrying out an accurate self-diagnosis to detect possible paraphilia. This system is capable of diagnosing 8 types of paraphilia with 31 symptoms.